(untitled) (Revista cientifica In Vestigium Ire, 2020)
"When I think with language, I don’t get ’meanings’ in addition to verbal expression; language itself is the vehicle of thought. L. Wittgenstein. Philosophical Research These two words that are cited to title this prologue, have been an invitation that is constantly repeated in this juncture scientifically called CONAVID 19 or commonly known as Coronavirus. But what is thinking intelligently? Is it not something that we do daily and almost unconsciously because it is considered an inherent quality of the human being? Then, why the invitation? Could it be that we are not being able to represent the circumstances that are surrounding us and therefore the solutions that they demand? To try to place, from a simple perspective to the reader within these two terms, it is necessary to take some definitions that, in addition, contribute to the purpose or objective that is intended to be achieved during the lines that make up the body and development of this prologue [...] Thinking could be said to be a faculty or simply the result of a process in which linguistics and symbols play an important role. Thinking is a skill woven from the experience of the world, from parallel levels and channels of perceptual and conceptual life. Finally, it is a skill that is restricted by social and cultural values. The acquisition of this skill requires not only experiences with things, but also social, affective and linguistic interactions (G. Edelman. Bright Air, Brilliant Fire. On the matter of Mind. Pages 173 and following). From a neuroscientific perspective: Possessing a mind means that an organism forms neural representations that can be converted into images, manipulated in a process called thinking, and eventually influence behavior by helping to predict the future, plan accordingly, and choose the next action. (A. Damasio. El Error de Descartes, Crítica, Barcelona, 1994) Intelligence. . . The human intelligence, framed in the principle of being an adaptive resource that has generated the human being in his evolutionary process. Human intelligence, generated in the evolutionary process of the species, has been capable of creating the best project, the way to do this or that, to relate among ourselves and with our natural environment, the best self that we can, the best of the possible worlds. He has deposited in these purposes the hope in a certain idea of humanity and progress, no longer biological but social" (Carlos Muñoz Gutiérrez, Towards a theory of the intelligent mind, Chap.7) In the situation that we currently find ourselves as humanity and community located in that great global village, to think intelligently becomes more than an invitation, a prevailing requirement, more so when we have seen in the previous paragraphs that, this capacity allows us to create our own means in front of diverse situations, which require solutions in a framework not clearly biological, but social, of reason, and logic. It is not enough to make this call to an individual intelligence but to a collective one and it is here where the University enters to play a relevant role, promoting its integral processes in a dynamic and evolutionary way, where innovation and team thinking, strengthens the teaching and learning process. We are going through a crucial moment for higher education, given the preventive social isolation to which we are subjected due to the pandemic that accompanies us and which resists abandoning us. Thinking intelligently then calls us to rethink our institutional and academic processes, and this in turn to conceive new strategies that respond to this present need with foresight and that have as a Presidium to guarantee quality academic training. In the case of Colombia, in relation to higher education institutions, whose modality is face-to-face, an arduous path of forced march had to be undertaken in order to continue with the work entrusted to the training of students, who have also had to face and confront, like the other actors in this process, the incorporation of ICTs in a tempestuous but essential manner so as not to see their academic process and therefore their life project interrupted. The adaptation that has been carried out, motivated by the situation, should not only be seen as an immediate response to the existing situation, but also to a need for efficient, highly competitive training that continues with the high quality that has been committed, and which is already demanded, by a digital economy that demands highly qualified professionals for its development and growth. There is no doubt that this new scenario with its clear challenges effectively and proactively calls for the interaction that must exist and be promoted in order to achieve that collective intelligent thinking that will allow us to share experiences, information and knowledge, providing new solutions that transform societies through new knowledge and lessons learned.